Robot Line Follower sebagai Alat Permainan Edukatif bagi Anak Usia Dini: Line Follower Robot as An Educational Game Media for Early Childhood - Sari, Wahyuni Eka; Triyono, Agus; Irwansyah; Utomo, Karyo Budi; Hakim, Ahmad Rofiq (Politeknik Negeri Samarinda, 2024)
Fine motor skills in children that involve movements using small muscles in the hands and wrists need to be trained through writing, eating, dressing, and playing activities. These skills develop gradually from birth to adulthood and require regular practice. One of the play activities to train fine motor skills in early childhood is assembling robots. This activity can improve children's fine motor skills, improve hand-eye coordination, dexterity, accuracy, strength, creativity, problem solving, and spatial awareness. The robot used in this activity is a line follower robot. There are 3 types of robots used in this activity. This activity was carried out with students of Kartika V-16 Samarinda Kindergarten which began with interviews with teachers, preparing activity materials, and presenting materials while practicing them with students and parents. The results of this activity show that assembling robots from used goods is not only fun, but also educational and improves the relationship between parents and children. This activity can also be an effective and fun way to introduce children to the world of technology and support the development of their essential skills.